Distribution of electric field in capacitor and surge arrester bushings - Illias, Hazlee Azil; Tunio, Mohsin Ali; Bakar, Ab Halim Abu; Mokhlis, Hazlie (2012)
The electric field distribution in high voltage capacitor and surge arrester bushings is principally dependent on the geometry dimension and types of the materials used. The main target is to achieve a bushing design which has a good electric field stress control. In this paper, two-dimensional (2D) axial-symmetrical model geometries of high voltage capacitor and surge arrester bushings have been developed using finite element analysis (FEA) method, which is COMSOL Multiphysics software. These models have been used to obtain the electric field distribution in capacitor and surge arrester bushing models. The effects of the bushing permittivity and electrical conductivity, the width and length and the metallic interface on the electric field distribution in bushing structure were analysed. From this study, an understanding of electric field distribution in bushing geometry may be attained, which may help in designing high voltage bushing stress control.